2017
DOI: 10.1063/1.4996410
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of thermopower in GaN by ion irradiation and possible mechanisms

Abstract: A detailed analysis of defect assisted transport properties of GaN after irradiation is carried out. Unintentionally doped GaN samples were irradiated by a 100 MeV oxygen ion beam and a 200 MeV silver ion beam at various fluences between 1 × 1010 ions/cm2 and 5 × 1011 ions/cm2. Thermopower and Hall effect measurements were done on pristine and irradiated GaN samples at variable temperatures. An increase in the thermopower with temperature as well as on irradiation (with respect to pristine GaN) was observed. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Both p-and n-type materials were successfully achieved depending upon the amount or type of the additional impurity introduced in the pure GaN material [24]. Our group previously reported enhancements in the Seebeck coefficient and power factor of n-GaN thin films and other materials by optimized ion beam irradiations [25,26]. Yamamoto et al prepared bulk GaN material with micron size of particles, which showed a negative S value of −50 μV/K at room temperature that further increased with temperature [27].…”
Section: Ztmentioning
confidence: 99%
“…Both p-and n-type materials were successfully achieved depending upon the amount or type of the additional impurity introduced in the pure GaN material [24]. Our group previously reported enhancements in the Seebeck coefficient and power factor of n-GaN thin films and other materials by optimized ion beam irradiations [25,26]. Yamamoto et al prepared bulk GaN material with micron size of particles, which showed a negative S value of −50 μV/K at room temperature that further increased with temperature [27].…”
Section: Ztmentioning
confidence: 99%
“…In these materials, it is expected that the thermal conductivity might be decreased by introducing the disorder with the short and longwavelength phonon scatterings for both low and high-temperature regimes. Similarly, in GaN controlled defect introduction by swift heavy ion irradiation have resulted in increased thermopower and power factor [15]. An optimized ion energy and fluence can improve the thermoelectric properties of β-Ga2O3.…”
mentioning
confidence: 99%
“…The concept of large E a over E s lies in such a way that in the resistivity measurements, the current flows through the film in a closed loop because the charge carriers need to overcome the highest potential barrier during the conduction. However, in thermopower, it is an open circuit measurements wherein the charge carriers have to cross only the local fluctuations 10,38 . The difference ΔE quantifies the magnitude of potential fluctuations.…”
Section: Resultsmentioning
confidence: 99%
“…To conclude, N ion implantation creates defects and vacancies, which affect the transport properties of the carriers. It modifies the transport mechanism by creating trap centers and defects which act as scattering centers 10 . The defects induced leads to the reduction of thermal conductivity and have less effect on S, which in turn improves the ZT value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation